Edison's Modern Legend in Villiers' L'Eve future - Ana Oancea (Nordlit: Tidsskrift i litteratur og kultur, 2012)
This paper analyzes the characterization of Thomas Edison in Villiers de l’Isle-Adam’s L’Eve future (1886) in an effort to explain how the author constructs this figure’s modern legend in the novel’s “oeuvre d’art-métaphysique.” Choosing an inventor protagonist in a work that recommends itself on its serious, artistic purpose stands out in late 19th century literature because, at the time, such characters are associated with popular literature. Villiers stresses the uniqueness of his Edison by suggesting comparisons with such literary and mythological precursors as Faust and Prometheus only to show that his protagonist has little in common with them: this inventor looks down upon humanity and wishes to reform it, while being arrogant and happy in his lucrative business.